ANALISIS PENGENDALIAN PERSEDIAAN DENGAN METODE EOQ (Studi Kasus pada Bahan Baku Beras di Warung Sorabi Teh Eneng) - Apriani, Della; Sutrisna, Arga; Muhamad Pauzy, Depy (LP2M Universitas Perjuangan Tasikmalaya, 2024)
ABSTRACT This study aims to find out how the implementation of raw material inventory control that has been carried out at Warung Sorabi Teh Eneng, how to apply the EOQ method in controlling raw material inventory at Warung Sorabi Teh Eneng and whether there is a difference between controlling raw material inventory at Warung Sorabi Teh Eneng without apply the EOQ method by applying the EOQ method. The main raw material used by Warung Sorabi Teh Eneng is rice. Warung Sorabi Teh Eneng processes rice into sorabi food. In this research at Warung Sorabi Teh Eneng, it uses interview data collection techniques, library research, and observation. The method applied in this research is the mixed methods method (combination method). The data analysis method applied is using Economic Order Quantity (EOQ), Safety Inventory, Reorder Point and Total Inventory Cost. Based on the results of this study, it is known that by calculating the EOQ method, the company can optimize inventory and can streamline inventory costs. And based on the results of the paired samples t-test, it is stated that there is a real/significant difference between the data results without applying the EOQ method and applying the EOQ method. Keywords: Inventory Control, Economic Order Quantity, Safety Stock, Reorder Point and Total Inventory Cost